Membangun Kesadaran Mempelajari Bahasa al-Quran Di Desa Bengkes Kecamatan Kadur Kabupaten Pamekasan - Supriyadi, Moh.; Holis, Nur; Zidan, Moh. Hamdan Yazid; Hannani, Rifqi; Sirojuddin, Sirojuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Talking about Islamic education, of course it cannot be separated from the Arabic language. As the language of the Qur'an and Sunnah which is the main source for understanding Islamic religious law, of course Arabic is one of the languages that must be mastered or at least understood by Muslims. As stated in the Qur'an: